Regioisomeric distribution of 9-and 13-hydroperoxy linoleic acid in vegetable oils during storage and heating - Pignitter, Marc; Zaunschirm, Mathias; Lach, Judith; Unterberger, Laura; Kopic, Antonio; Kessler, Claudia; Kienesberger, Julia; Pischetsrieder, Monika; Eggersdorfer, Manfred; Riegger, Christoph; Somoza, Veronika (Journal of the Science of Food and Agriculture, 2018)
CONCLUSIONA temperature-dependent distribution of HpODE regioisomers could be shown in vegetable oils, suggesting their application as markers of lipid oxidation in oils used for short-term heating. (c) 2017 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.
Keywords: lipid hydroperoxides; linoleic acid; heating; storage; vegetable oil